Development and Sustainability India in a Global Perspective - Banerjee, Sarmila.; Banerjee, Sarmila.; Chakrabarti, Anjan.; Chakrabarti, Anjan. (Springer India : Imprint: Springer, 2013)
Following the reforms undertaken in the last two decades, India’s economic landscape has been radically transformed. This book examines the new economic map, which is shown to be shaped by two intertwined currents: globalization and sustainability. Weaving extensively through these currents and the canvas of development in the Indian economy they open up, this work seeks to introduce new methodologies, a corpus of concepts and modes of analysis to make sense of the emerging order of things. What transpires in the course of the investigation is a critical reflection of the present in which not only the new institutions, policies and practices are analyzed, but their limitations, fragility and at times myopic approaches are brought to light. By highlighting the rough edges created by the new conditions, this book is firmly engaged with the frontier of the Indian economy and ends up challenging many well-known conjectures and assumptions. In doing so, it strives to shift the Indian economy to a new terrain, thereby fundamentally re-locating and re-orienting the discourse of that economy as a unique object of analysis.